Design of a Robust ESD Protection Device using 6H-SiC Nano-Scale GGNMOS - Chowdhury, Shirazush Salekin; Farhadur Arifin, (AIUB Journal of Science and Engineering (AJSE), 2021)
—With the continuous shrinking of the technological nodes and the introduction of new device concepts and materials, integrated circuits (IC) are becoming more vulnerable to electrostatic discharge (ESD) induced failures which is one of the major concerns in designing robust ICs. Therefore, to improve the reliability of the ICs against ESD induced failures, extensive research efforts are being conducted. In this paper, we have presented a 6H-SiC based nano-scale grounded-gate NMOS (ggNMOS) ESD protection device and compared the results with the 3C-SiC-based ggNMOS. To design a robust ESD protection device, some critical device parameters, such as substrate doping concentration, source/drain doping concentration, drain to substrate contact spacing, and substrate contact resistance should be optimized. The ESD protection characteristics can be improved by utilizing the near punch-through effect. It was found that the trigger voltage and hold voltage are higher in 6H-SiC than the 3C-SiC having identical device parameters. 6H-SiC shows better voltage clamping performance as the turn-on resistance of 6H-SiC is smaller compared to the 3C-SiC material. Therefore, the results show that 6H-SiC has a better performance compared to 3C-SiC and due to its higher bandgap, and can be used as a good ESD protection device. All the simulations are carried out using the Silvaco ATLAS device simulator.